2017
DOI: 10.1038/s41598-017-04219-1
|View full text |Cite
|
Sign up to set email alerts
|

Transmembrane Interactions of Full-length Mammalian Bitopic Cytochrome-P450-Cytochrome-b5 Complex in Lipid Bilayers Revealed by Sensitivity-Enhanced Dynamic Nuclear Polarization Solid-state NMR Spectroscopy

Abstract: The dynamic protein-protein and protein-ligand interactions of integral bitopic membrane proteins with a single membrane-spanning helix play a plethora of vital roles in the cellular processes associated with human health and diseases, including signaling and enzymatic catalysis. While an increasing number of high-resolution structural studies of membrane proteins have successfully manifested an in-depth understanding of their biological functions, intact membrane-bound bitopic protein-protein complexes pose t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
38
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 106 publications
(192 reference statements)
1
38
0
Order By: Relevance
“…Recent experimental and computational evidences on the lateral organization of microsomal cytochrome P450 pointed to a strong interaction of both TMD and soluble domain with the lipid bilayer. [13, 15, 21, 29, 33] The results presented here also provide significant molecular insights into the factors governing P450 ligand affinity for hydrophobic molecules. Further, the innovative combination of peptide-based nanodiscs and 31 P NMR experiments to quantitatively determine the different type of lipids constituting nanodiscs will be useful to study a variety of membrane proteins (like GPCR and pore-forming proteins [35] ) and membrane-assisted amyloid aggregation.…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…Recent experimental and computational evidences on the lateral organization of microsomal cytochrome P450 pointed to a strong interaction of both TMD and soluble domain with the lipid bilayer. [13, 15, 21, 29, 33] The results presented here also provide significant molecular insights into the factors governing P450 ligand affinity for hydrophobic molecules. Further, the innovative combination of peptide-based nanodiscs and 31 P NMR experiments to quantitatively determine the different type of lipids constituting nanodiscs will be useful to study a variety of membrane proteins (like GPCR and pore-forming proteins [35] ) and membrane-assisted amyloid aggregation.…”
mentioning
confidence: 79%
“…[7] Also, lipid membrane is the main access pathway for hydrophobic substrates, playing a critical role in P450 drug-metabolism and pharmacokinetics. [812] There is mounting evidence that protein-protein interactions are also driven by cross-talking between transmembrane domains (TMD), [1315] which further amplifies the role of lipids on P450’s structural stability and function. Thus, there is a need for new biophysical tools that can enlighten such presently precluded dynamics, and provide critical knowledge on P450’s function.…”
mentioning
confidence: 99%
“…CPR contains a highly disordered region in the N-terminus preceding the helical transmembrane domain; CPR's high lateral mobility is probably related to its different topology compared to P450. [14] Our solution NMR experiments have revealed the interacting interface in the soluble domains of the cytb 5 -P450 complex. [24] We revealed that, similar to P450, cytb 5 is indeed a bitopic membrane protein with a cytosolic domain not interacting with the membrane surface, and exhibit fast time scale of motion (~microsecond or faster).…”
Section: Structure and Function Of Cytochrome P450mentioning
confidence: 85%
“…CPR is a large (~78 kDa) flavoprotein with a flavin adenine dinucleotide (FAD) and a flavin mononucleotide (FMN) domains connected via a hinge region. [14,25] In addition, our recent dynamic nuclear polarization (DNP) based magic angle spinning (MAS) solid-state NMR experiments revealed that the two transmembrane domains interact in the cytb 5 -P450 complex and have a cross at the leucine zipper region of cytb 5 . [11][12] Cytb 5 is instead a small (~15 kDa) hemeprotein, whose full-length membranebound high-resolution structure and topology were determined by our group using a combination of solution and solid-state NMR techniques.…”
Section: Structure and Function Of Cytochrome P450mentioning
confidence: 99%
See 1 more Smart Citation